Adolescent health behaviors, family socioeconomic status and health as risk factors for tendon ruptures in adulthood: a longitudinal study - Teuho, Alisa; Vaajala, Matias; Ponkilainen, Ville; Koivusilta, Leena; Rimpelä, Arja; Mattila, Ville M. (Springer Science and Business Media LLC, 2026)
Introduction
The incidence of tendon ruptures has increased in recent years highlighting the need of better understanding their causes and prevention strategies. This study aims to investigate the influence of adolescent health behaviors (smoking, alcohol use, physical activity), health (self-reported chronic disease, overweight), and family socioeconomic status (SES) (parental occupational status and educational level) on later tendon ruptures until middle age in Finnish adolescents.
Materials and methods
The baseline data were surveys gathered biennially in 1981–1997 (the Adolescent Health and Lifestyle Survey) and linked individually with diagnoses of tendon ruptures (Achilles, quadriceps, hamstring, biceps tendon, and rotator cuff) retrieved from the Care Register for Health Care. A logistic regression model was used to analyze the associations between adolescents’ health behaviors, health and family socioeconomic status on later tendon rupture. Adjusted odds ratios (aOR) with 95% confidence intervals (CIs) were computed.
Results
Total of 42 971 persons were included in the analyses. The mean follow-up time was 25.2 years and during the follow-up 685 tendon ruptures occurred. Males were more likely to incur tendon rupture. The mean age at the time of tendon rupture was 36.6 years. Frequent activity in sports clubs increased the odds of tendon rupture (2 to 3 times a week or less aOR 1.73, CI 1.45–2.05, 4 or more times a week aOR 3.54, CI 2.88–4.32). The association was seen in both genders. Daily smoking, alcohol use, physical activity in leisure time, overweight, chronic disease, or parental socioeconomic status in adolescence were not associated with the risk of tendon rupture.
Conclusion
Frequent participation in sports clubs during adolescence increased the risk of tendon rupture in adulthood, while leisure time physical activity did not. Health compromising behaviors (smoking, alcohol use, overweight) or chronic diseases in adolescence does not seem to play a role in later tendon ruptures until middle age.